The Potential of Moringa oleifera Extract Waste as Fe Adsorbent in South Sumatra, Indonesia - Syarifah Syarifah; Ra Hoetari Tirta Amelia; Riri Novita Sunarti; Awalul Fatiqin; Yahya Febrianto; Thathit Suprayogi; Yithro Serang (Biota, 2023)
The issue of environmental pollution has become a concern, especially for the government, since the establishment of Law No. 4 of 1982. This is because the effects of pollution can be toxic and even fatal for living beings, particularly humans. One of the pollutants in the environment generated from mining industry waste is heavy metal Fe. In light of these problems, a study was conducted to investigate the effectiveness of sawdust and Moringa twigs as by-products in adsorbing heavy metal iron (Fe) in the liquid waste of the gold mining industry. This research is classified as pure experimental research. The research reveals that the mean percentage reduction in the heavy metal iron (Fe) content in the gold mining industry wastewater, after treatment with the addition of Moringa leaf powder, is 9.6%. On the other hand, treatment with the addition of Moringa stem powder achieves a reduction of 92%. This significant difference is attributed to the bioactive compound rhamnosyloxy-benzyl isothiocyanate present in Moringa. This compound has the ability to adsorb and neutralize sludge and metal particles found in the waste suspension, along with dirt particles in the water. Consequently, Moringa shows potential as a natural coagulant for water purification purposes.